Which part of the expression is a constant 3x + 4

Answers

Answer 1
Answer: the constant of the fraction is the 4

Related Questions

Jake is applying to rent an apartment. Which information about Jake could appear on his credit report?Choose all answers that are correct. A. the country where he was born B. the fact that he made two late mortgage payments C. the credit limits on his credit cards D. his social security number
Molly is on a game show. To win $1,000,000, she must answer this question: What key features are necessary—and how are the features used—to create the sketch of a polynomial function? What is Molly's winning answer? Explain in complete sentences.
What’s the perimeter and area
Johanna purchases a book for $14.95. There is a sales tax of 6.5%. How much is the final price with tax? What is the total? What is the percent? Use the formula amount = total x percent to find the amount of the sales tax. To find the final price, add the cost of the book to the amount of tax.
If m<1=140, what is m<3

What is the tenth term in the sequence 5,8,11,14...?

A. 29

B.32

C. 35

D. 38

Answers

cause 5+3+8, 8+3=11 11+3=14, so 14+3=17 17+3=20, 20+3=23 23+3=26 26+3=29 29+3=32
so its 5, 8, 11, 14, 17, 20, 23, 26, 29, 32
so the answer is 32
Since the sequence is adding 3 to each number, 5+3=8, 8+3=11, 11+3=14, 14+3=17, 17+3=20, 20+3=23, 23+3=26, 26+3=29, 29+3=32, 32 is the answer since it is the tenth term in sequence.

What does one half divided by four equal?

Answers

the answer is 1/8 or 0.125 or it can be 12.5%
1/2/4=
1/2*1/4
=1/8
20 charrr

Which solid figure has one polygon base?

pyramid
cone
cylinder
prism

Answers

Answer:

pyramid

hope this helped! :)

Answer:

Your answer is a pyramid.

Step-by-step explanation:

While a cone also only has one base, it's base is a circle, which is not considered a polygon. The other two choices have two bases.

Consider the following pair of equations:x + y = –2
y = 2x + 10

If the two equations are graphed, at what point do the lines representing the two equations intersect?


(–4, 2)
(4, 2)
(–2, 4)
(2, 4)

Answers

Asking the Math Gods...


x=-4
y=2

The 2 lines will cross at what is called the "point of intersection" It is the (x, y) coordinates that are the same for line one and line two.  Since the coordinates are equal, we can set them equal to one another in the equations and solve for the value... Let me show you...

We set the y coordinates equal to one another first.  Since they give us one of the y coordinates as y = 2x + 10, we use it in the other equation so we can solve for the x coordinate...

x + y = -2

Since y = 2x + 10 then

x + 2x + 10 = -2
3x + 10 = -2
3x = -12
x = -12/3 = -4

Now that we have a value for the x coordinate, we can substitute it back into one of the equations to solve for the y coordinate...

x + y = -2
-4 + y = -2
y = -2 + 4
y = 2

So you now have the x and y coordinates that are the same for each equation, so that is the point of intersection...

(-4, 2)

Which word best describes the degree of overlap between the two data sets?A.
high

B.
moderate

C.
low

D.
none

Answers

The right answer for the question that is being asked and shown above is that: "C. Low." The word that best describes the degree of overlap between the two data sets is low. The overlap is not that big enough or nothing at all. It is just low.

Show work
solve x^2-6x= -25

Answers

Answer: x = 3 ± 4i

Step-by-step explanation:

 x² - 6x + 25 = 0

a=1  b= -6  c=25

Use Quadratic Formula:

x = \frac{-b +/- \sqrt{b^(2)-4ac}}{2a}

= \frac{-(-6) +/- \sqrt{(-6)^(2)-4(1)(25)}}{2(1)}

= (6 +/- √(36-100))/(2)

= (6 +/- √(-64))/(2)

= (6 +/- 8i)/(2)

= (2(3 +/- 4i))/(2)

  = 3 ± 4i


Answer:

x= 3+4i , x= 3-4i

Step-by-step explanation:

x^2-6x= -25

To solve for x  we need to make right hand side

So add 25 on both sides

x^2-6x+25=0

Now apply quadratic formula

x=(-b+-√(b^2-4ac))/(2a)

From the given equation a=1, b=-6  and c=25

Plug in all the values in the formula

x=(-(-6)+-√((-6)^2-4(1)(25)))/(2(1))

x=(6+-√(-64))/(2)

We know  √(-1) =i

So equation becomes

x=(6+8i)/(2)

Divide by 2

x= 3+-4i

So x= 3+4i , x= 3-4i